2017
DOI: 10.26417/ejms.v4i3.p7-23
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Servant Leadership Instrument for Social Enterprise (Cooperative)

Abstract: The purpose of this paper is to describe the development and validation of a multi-dimensional instrument to measure servant leadership in social enterprise (cooperative) context. Based on an extensive literature review, expert's judgment and Exploratory Factor Analysis (EFA), 57 items were formulated and only 27 items yielding to five factors: doing right things, develop vision with others, democratic, develop others potential and develop community. The construct develops purposely for social enterprise (coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…This does not mean that SL and SE are conceptually and empirically undistinguishable. They belong to different disciplines and research domains, as well as different social and organizational levels (Latiff, Majid, & Mohamad, 2017; Petrovskaya & Mirakyan, 2017). SE behaviours relate to looking for, identifying and using opportunities to produce social changes, while SL refers to the relationship between leader and follower within organizations.…”
Section: Servant Leadership and Sementioning
confidence: 99%
See 1 more Smart Citation
“…This does not mean that SL and SE are conceptually and empirically undistinguishable. They belong to different disciplines and research domains, as well as different social and organizational levels (Latiff, Majid, & Mohamad, 2017; Petrovskaya & Mirakyan, 2017). SE behaviours relate to looking for, identifying and using opportunities to produce social changes, while SL refers to the relationship between leader and follower within organizations.…”
Section: Servant Leadership and Sementioning
confidence: 99%
“…El liderazgo de servicio implica algunas de esas capacidades, lo cual no quiere decir que emprendimiento social y LS sean conceptual y empíricamente indistinguibles. Ambos pertenecen a una disciplina y un área de investigación distintas, y también a distintos niveles sociales y organizativos (Latiff, Majid, & Mohamad, 2017; Petrovskaya & Mirakyan, 2017). Los comportamientos de emprendimiento social se relacionan con la búsqueda, identificación y uso de oportunidades para producir cambios sociales, mientras que el liderazgo de servicio hace referencia a la relación entre el líder y sus seguidores dentro de una organización.…”
Section: Predicción De Las Actitudes Y Las Intenciones Conductuales H...unclassified
“…Servant leadership is a leadership style that was introduced by Robert K. Greenleaf to prioritise the followers" interests over the will of the leaders in the management (Ingram, 2016). This study adopts six important characteristics of servant leadership, which were identified to influence a better change implementation, namely humility, authenticity, empowerment, stewardship, accountability, and courage (Latiff et al, 2017). Practically, this leadership style is meant for Christianity (Gandolfi and Stone, 2018) but it was expanded to other religions" practicality such as Islam (Jabarkhail, 2020).…”
Section: Servant Leadership As a Mediator To Implement Green Manufact...mentioning
confidence: 99%
“…There are few empirical research that relate entrepreneurship with servant leadership and it is also difficult to find research about servant leadership instrument in higher education. Some of the previous studies correlate servant leadership with social entrepreneurship and social enterprise, such as the research conducted by [26], [27], [20]. [36] proposes servant leadership approach in the academic environment rather than other type of leadership.…”
Section: Th Icoen 2019mentioning
confidence: 99%